Dexketoprofen – an additional opportunity to control chronic pain syndrome in malignant neoplasms - I. A. Koroleva (Медицинский совет, 2019)
Chronic pain syndrome (CPS) is an independent disease. Patients with disseminated malignant tumors may experience chronic pain even with successful anticancer therapy. For the control of CPS use the WHO analgesic ladder. Despite adequate pain relief, patients may experience breakthrough pain. Clinical guidelines suggest the use of opioids for the treatment of breakthrough pain. Dexketoprofen is a nonsteroidal anti-inflammatory drug (NSAIDs) of rapid action. The drug is highly effective for pain in the bones of various origins. Dexketoprofen can be used for incident predictable breakthrough pain.